EFEKTIVITAS PEMBELAJARAN DARING MENGGUNAKAN GOOGLE CLASSROOM TERHADAP MINAT BELAJAR MATEMATIKA PADA SISWA SEKOLAH DASAR - Bella Damayanti (Undiksha, 2021)
The aim of this study was to find out the effectiveness of using Google classroom during online learning toward students' elementary Interest in math learning. The study adopt descriptive quantitative Which focus on students' interest during online learning. the partisipant for the study were elementary student on Banten province that were using Google classroom during online learning. The students were choose by Random sampling technique. The instrument to collect the data was using quesioner on google form. Data was analysis by using prosentase uji. The results of the study showed that online learning using google classroom on interest in learning mathematics in elementary school students has been effective. This is indicated by the acquisition of an average score for indicators of interest in learning mathematics using Google Classroom (61%), the use of Google Classroom features (72%) and the effectiveness of online learning using Google Classroom (62%). Although there are still students disagree that online learning is not effective (4.4%).